Kombinasi Ekstrak Etanolik Kunyit dan Temulawak Lebih Berpotensi sebagai Fitofarmaka Hepatoprotektif: Studi Efek Hepatoprotektif pada Mencit Balb/C yang Diinduksi Parasetamol - Nirmala, Atika Zahro; Widjokongko, S. Bambang; Budiani, Dyah Ratna (Nexus Biomedika, 2013)
The occurrence of liver damage especially caused by consuming non steroidal anti inflammatory medicine is high in some countries. In the other hand, turmeric and curcuma are frequently consumed as a herbal treatment. Those herbals contain antioxidant. The purposes of this experiment were to know the differences of hepatoprotective effect of ethanolic extract of turmeric, curcuma, and the combination of both in mice Balb/C induced by paracetamol. This research was a laboratory experimental study with the post test only control group design. The research used 25 male Balb/C mice that were devided into 5 groups: negative [KK (-)] and positive control group [KK (+)] were administered 0.2 ml of aquades, while group treatment 1 (KP1), 2 (KP2) and 3 (KP3) consecutively Â were administered 2.8 mg of turmeric ethanolic extract, 14 mg of curcuma ethanolic extract and the combination of 1.4 mg of turmeric extract and 7 mg of curcuma ectract. The treatments were conducted in 14 days. The dose of paracetamol toxic was treated to KK (+), KP1, KP2, and KP3 on the 12th, 13th, and 14th days. Hepatoprotective effect was assessed by the number of disfunctional cells of liver. The data were analyzed by One Way ANOVA and LSD test. The result of one way ANOVA showed a significant difference in the five groups with p = 0.03. LSD test showed a significant difference among KK (-), KP1, and KP3 against KK (+) and KP2. There were some differences of the hepatoprotective effect of ethanolic extract of turmeric, curcuma, and the combination of both in mice Balb/C induced by paracetamol. Keywords: hepatoprotective, turmeric, curcuma, paracetamol consecutively